Protection of Information and the Right to Privacy - A New Equilibrium?
XVII, 144 p. 12 illus.
Keywords: This book presents the latest research on the challenges and solutions affecting the equilibrium between freedom of speech, freedom of information, information security, and the right to informational privacy. Given the complexity of the topics addressed, the book shows how old legal and ethical frameworks may need to be not only updated, but also supplemented and complemented by new conceptual solutions. Neither a conservative attitude (“more of the same”) nor a revolutionary zeal (“never seen before”) is likely to lead to satisfactory solutions. Instead, more reflection and better conceptual design are needed, not least to harmonise different perspectives and legal frameworks internationally. The focus of the book is on how we may reconcile high levels of information security with robust degrees of informational privacy, also in connection with recent challenges presented by phenomena such as “big data” and security scandals, as well as new legislation initiatives, such as those concerning “the right to be forgotten” and the use of personal data in biomedical research. The book seeks to offer analyses and solutions of the new tensions, in order to build a fair, shareable, and sustainable balance in this vital area of human interactions.